Lung Cancer and Interstitial Lung Diseases: A Systematic Review - Kostas Archontogeorgis; Paschalis Steiropoulos; Argyris Tzouvelekis; Evangelia Nena; Demosthenes Bouros (Pulmonary Medicine)
Interstitial lung diseases (ILDs) represent a heterogeneous group of more than two hundred diseases of either known or unknown etiology with different pathogenesis and prognosis. Lung cancer, which is the major cause of cancer death in the developed countries, is mainly attributed to cigarette smoking and exposure to inhaled carcinogens. Different studies suggest a link between ILDs and lung cancer, through different pathogenetic mechanisms, such as inflammation, coagulation, dysregulated apoptosis, focal hypoxia, activation, and accumulation of myofibroblasts as well as extracellular matrix accumulation. This paper reviews current evidence on the association between lung cancer and interstitial lung diseases such as idiopathic pulmonary fibrosis, sarcoidosis, systemic sclerosis, dermatomyositis/polymyositis, rheumatoid arthritis, systemic lupus erythematosus, and pneumoconiosis.